Respuesta :
The answer is D because when finding the value for x, it equals 0. When you substitute 0 in the equation (-1/3)x+4, y=4.
The answer is D, because
3y-x=12, as said in the problem;
so x=3y-12.
y=-1/3x+4, as said in the problem.
so, we can use x=3y-12 to replace the x in the equation: y= -1/3(3y-12)+4
y= -1/3x3y+1/3x12+4
= -y+4+4 then
y= -y+8.
2y=8
so y=4.
To find x, we can use x=3y-12 (see line 3.)
x=3x4-12
so x=0
Therefore, the answer is x=0, y=4 which is answer D (0,4).
3y-x=12, as said in the problem;
so x=3y-12.
y=-1/3x+4, as said in the problem.
so, we can use x=3y-12 to replace the x in the equation: y= -1/3(3y-12)+4
y= -1/3x3y+1/3x12+4
= -y+4+4 then
y= -y+8.
2y=8
so y=4.
To find x, we can use x=3y-12 (see line 3.)
x=3x4-12
so x=0
Therefore, the answer is x=0, y=4 which is answer D (0,4).